How to uphold a Human Right in the World and Indonesia? A Book Review Hukum Hak Asasi Manusia, Rahayu Hartini, Badan Penerbit Universitas Diponegoro, Semarang, 2015, 408 Pages, ISBN 978-979-70490-6-5 - Al Izhar, Mohammad Yufi (Indonesian Journal of Advocacy and Legal Services, 2021)
Human Rights are basically universal and their rights cannot be taken and revoked by anyone. This is interpreted no matter how bad a person's behavior, a person will still be considered as human as they should be, and will continue to have their rights as human beings, which means that their human rights are inherent and will always be permanently attached to him. Human Rights (HAM) are believed to be the right of life naturally possessed by every human being without exception and a special human thing such as class, group, or social level. Human Rights have basically been championed by humans in all parts of the world throughout the ages. The book written by Prof. Dr. Rahayu, which is very intended for both Faculty of Law students and non-Faculty of Law students, provides an answer to the doubts of the public regarding Human Rights that actually occur in Indonesia and internationally. She also explained the meanings of the struggle of each country that issued their public opinion in the interest of the International, this meant that something that happened in the international arena was certainly a collection of perceptions of settlement within a country. Therefore, Human Rights Law cannot be separated from the main supporting factors which are the material of the countries that make the agreement.